So clean;lord leverhulme, soap and civilisation. (MANCHESTER UNIV Press, 2017)
This book is an unorthodox biography of William Hesketh Lever, 1st Lord Leverhulme (1851-1925), the founder of the Lever Brothers' Sunlight Soap empire. Unlike previous biographies, which have focused on the man's life story and eccentricities, or just considered one aspect of his career, So clean places him squarely in his social and cultural context and is fully informed by recent historical scholarship. Much more than a warts-and-all biography, the book uses Lever as an entry-point for contextualized and comparative essays on the history of advertising; on factory paternalism, town planning,